ENERGY-CONSUMPTION ROUTING PROTOCOLS FOR WIRELESS SENSOR NETWORK - Dr. TanajiA. Dhaigude (International Journal of Innovations in Engineering Research and Technology, 2022)
The Major problem in wireless sensor network to achieve an energy-efficient routing protocol. Energy consumption is a critical problem in wireless sensor network for nodes and network life. For increasing lifetime of networks energy saving is must and also energy saving routing protocols are very important in wireless sensor networks. More the radius cover more is energy requirement. Hence if radius is less then energy consumption will be less. In this Paper, a RSES routing protocol is presented which adjusts the radius according to threshold value. By using this protocol, energy consumption is minimized. The on-demand route discovery process issued for routing table information. When the remnant energy reaches a certain threshold, the node reduces its transmission radius and again readjustment is done in order to achieve less energy consumption under the premise of some certain coverage ratio .Hence by using this algorithm Energy consumption can be minimized. Using RSES protocolnetwork lifetime increases and achieves a balanced networkload,energysavingandroutingtraffic. Usingshortestpathalgorithmswemight get the energy efficient path but if the same path is used frequently then nodes on the same path gets discharged accordingly.EnergyKey terms: Wireless Sensor Network, Radius Self-Adjust Energy Saving Routing Protocol, CoverageRatio,Power saving,WirelessCommunication